Answer:
-54.3
Step-by-step explanation:
4(1.5−6.2)−4.5−31
=(4)(−4.7)−4.5−31
=−18.8−4.5−31
=−23.3−31
=−54.3
Answer:
{x,y,z} = {-18,4,2}
Step-by-step explanation:
Solve equation [2] for the variable x
x = -10y + 2z + 18
Plug this in for variable x in equation [1]
(-10y+2z+18) + 9y + z = 20
- y + 3z = 2
Plug this in for variable x in equation [3]
3•(-10y+2z+18) + 27y + 2z = 58
- 3y + 8z = 4
Solve equation [1] for the variable y
y = 3z - 2
Plug this in for variable y in equation [3]
- 3•(3z-2) + 8z = 4
- z = -2
Solve equation [3] for the variable z
z = 2
By now we know this much :
x = -10y+2z+18
y = 3z-2
z = 2
Use the z value to solve for y
y = 3(2)-2 = 4
Use the y and z values to solve for x
x = -10(4)+2(2)+18 = -18
Answer:
-2y2 - 4y - 7
Step-by-step explanation:
2y2 + 2y2 - 6y2 - 4y - 5 - 3 + 1
4y2 - 6y2 - 4y - 8 + 1
-2y2 - 4y - 7
Answer:
10
Step-by-step explanation:
A= L²
50 = L² (do opposite operation to find L)
L = 7.07
x²= L²+ L²
x²= 7.07² + 7.07²
x² = 100 ( do opposite operation to make x the subject)
x = 10
Note: opposite operation of square is square root